Avanços na Fruticultura Tropical no Brasil - Meletti, Laura Maria Molina; Sampaio, Aloísio Costa [UNESP]; Ruggiero, Carlos [UNESP] (FapUNIFESP (SciELO), 2011)
The main aspects that defined the evolution of technical crops of pineapple, papaya and passion fruit in Brazil have been discussed. In pineapple, it has been observed an innovative commercialization system of the Smooth Cayenne cultivar, which is the use of corrugated cardboard boxes for the domestic market, whose aim is to provide a flavor guarantee introduced into a brand. The recent release of cultivars resistant to fusariosis, by Embrapa (Imperial and Victoria) and IAC (Fantastico) brings new perspectives for productivity. In passion fruit, the greatest contribution to the orchards was given by genetic breeding, initially focused only to increase crop productivity. In the early 2000, the launch of the first cultivars of passion fruit - more productive and with fruit quality distinguished for two different market segments (fresh fruits and agribusiness), transformed the Brazilian productive scenario. By creating an organized system of production and commercialization of selected seeds and seedlings, increased significantly the quality of the orchards. Nowadays, the availability of new cultivars tolerant to virus (VEFM) and regional varieties started to represent a difference for the culture. In papaya, stands out the occurrence of the Papaya Tree Mosaic (Monte Alto, SP, 1967), which determined the migration of culture by the state and their expulsion to other states, until its settling in Bahia and Espirito Santo, the largest national producers. It was compared the techniques used in different production periods, before and after the emergence of the mosaic, which allowed Brazil to set out on the international market, becoming the largest exporter of papaya, with productive crops and fruits of excellent quality. In this evolution, sum up the contribution of genetic improvement, which provided high-quality seed with reflects on cultural practices and propagation. Different harvesting and post-harvest techniques that result in improvements in the standard of quality of fruit exported to the European market and the U.S. are presented.
Progress in the Brazilian tropical fruitculture
Keywords: Fruitculture advances; Papaya; Passion fruit; Pineapple; Production technology